DAMPAK PELAKSANAAN EVENT INTERNASIONAL SAIL INDONESIA TERHADAP PERKEMBANGAN WISATA BAHARI INDONESIA - Saputra, Heldi; Harto, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of this research is to understand This research will discuss about the implementation of the International Event Sail Indonesia to the development of the capacity of Indonesian marine tourism. As we know, Indonesia is an archipelago (archipelago state) in the world that is located flanked by two oceans, the Pacific Ocean and the Indian Ocean. Indonesia has a wealth of natural resources, especially tourism. in addition to bali, Indonesia also has other tourist destinations that also has a high value. The tourism such as Wakatobi, Belitung, Morotai, Pulau Komodo, and Raja Ampad based in International Event Sail Indonesia in 2011 – 2014.This research theoretically has built with Globalism perspectives on International Relations and supported by International Tourism theory. Formulation of all arguments, facts, and theoretical framework on this research is guided by qualitative explanation methods. Technique in this research is through by the study of library. Data which is gotten and collected through the journal books, the last thesis and then from internet has related to the problems.Researcher has formulated answered-hypothesis whic reveals the fact that Sail Indonesia International Event Impact on Tourism Development Bahari Indonesia is the increasing domestic and foreign tourists visit in the object of the event. Either Wakatobi-Belitung (2011), Morotai (2012), Komodo Island (2013), and Raja Ampat ( 2014) been increase since that international event Sail Indonesia. development of domestic and foreign tourists visit also helped the development and the regional economyKeywords : International Event, Tourism, Tourist, Sail Indonesia, Sail Wakatobi-Belitung, Morotai, Komodo Island, Raja Ampat